2019
DOI: 10.1590/s0100-83582019370100140
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Volunteer Corn from Different Origins and Emergence Time on Soybean Yield and Stress Metabolism

Abstract: Volunteer corn occurrence with soybean is favored by the glyphosate-resistant (GR) corn cultivation preceding soybean and no-tillage systems. Volunteer corn interference causes significant losses in soybean grain yield. The levels of crop losses change with the corn density, origin, and time of emergence. High levels of weed interference in crops can result in the production of reactive oxygen species and lead to the occurrence of oxidative stress. The objectives of this study were to evaluate the effects of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The results of the highly competitive potential of voluntary maize plants interspersed with soybean were similar to those obtained by Rizzardi, Piasecki, Schons, Caverzan, and Langaro (2019), where competition from nine voluntary maize plants per m 2 reduced soybean yields by 75.9%. Alms et al (2016) observed a 71% reduction in soybean yield due to the presence of six maize plants per m 2 in repeated experiments with two different crops.…”
Section: Voluntary Maize Interference On Soybean Cropsupporting
confidence: 81%
“…The results of the highly competitive potential of voluntary maize plants interspersed with soybean were similar to those obtained by Rizzardi, Piasecki, Schons, Caverzan, and Langaro (2019), where competition from nine voluntary maize plants per m 2 reduced soybean yields by 75.9%. Alms et al (2016) observed a 71% reduction in soybean yield due to the presence of six maize plants per m 2 in repeated experiments with two different crops.…”
Section: Voluntary Maize Interference On Soybean Cropsupporting
confidence: 81%
“…The grain losses at harvest of these crops have caused an expansion in the incidence of volunteer plants in the succession crop. They can compete for space, water, nutrients, light, and host pests and diseases (Alms et al, 2016;Petter et al, 2016;Piasecki & Rizzardi, 2018;Rizzardi et al, 2019).…”
mentioning
confidence: 99%